Որոշ հայ նշանավոր տոհմերի ծագումը ըստ ավանդական տվյալների - Պետրոսյան, Արմեն («Նաիրի» հրատ.)
The article discusses the legends about the origins of some ancient Armenian royal and princely families: the Eruandunis, the Bagratunis, the Artsrunis and the Slkunis. The Bagratunis originate from the god Angeł, while the Artsrunis from the King Sennacherib of Assyria, who, being the second eponym of the city of Angeł, may be regarded as the epic version of the god Angeł. The legendary eponyms of the Eruanduni and Slkuni families are described by the word džneay ‘fierce’ (referring to the glance), which in myths is presented as a characteristic of the god Angeł. This shows that they also share the same origin. It is likely that all these princely houses constituted the branches of the royal Eruanduni dynasty (C. Tumanoff). Accordingly, the origin from the god Angeł was, in all probability, initially attributed to the Eruandunis. В статье рассматриваются легенды о происхождении некоторых древнеармянских царских и княжеских семей: Ервандуни, Багратуни, Арцруни и Слкуни. Багратуни возводятся к богу Ангеху, Арцруни к царю Сеннахерибу Ассирийскому, который, в свою очередь, как второй эпоним города Ангеха, может рассматриваться как эпическая версия бога Ангеха. Легендарные эпонимы родов Ервандуни и Слкуни описываются словом džneay «свирепые» (имеется в виду взгляд), что в мифах выступает как характеристика бога Ангеха. Это показывает, что им приписывалось то же происхождение. Вполне вероятно, что все эти княжеские дома составляли ветви царской династии Ервандуни (K. Туманов). Соответственно, происхождение от бога Ангеxa скорее всего первоначально относилось к Ервандуни.
Keywords: Աղբյուրագիտություն; Պատմագրություն; Տոհմաբանություն